USE OF CANNABIS FOR MEDICINE (JHON FISKE SEMIOTIC ANALYSIS) - Fikri, M. Andi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Film is an integral part of mass communication, and in its purpose film itself as a message in conveying and offering more than just sound and meaningful images. Recently, the phenomenon of legalizing marijuana has often been discussed and constructed through the media. One of them is the documentary